2005
DOI: 10.1002/xrs.800
|View full text |Cite
|
Sign up to set email alerts
|

Portable x-ray fluorescence spectrometer with a pyroelectric x-ray generator

Abstract: A portable x-ray fluorescence spectrometer was assembled with an x-ray generator that was driven by a 9 V dry electric battery. Several possible optimum geometries of the x-ray generator and detector were evaluated, and the results showed that the intensity of fluorescent x-rays was strong enough when the angle between the x-ray generator and detector was as small as 30 • . The geometrically optimized x-ray spectrometer was applied to the analysis of paints, plastics and aluminum foils. Pigments in paint and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The details of the X-ray source utilized were reported in a previous paper, 8,19 and are shortly summarized as follows: (1) 848 ANALYTICAL SCIENCES JULY 2008, VOL. 24…”
Section: Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the X-ray source utilized were reported in a previous paper, 8,19 and are shortly summarized as follows: (1) 848 ANALYTICAL SCIENCES JULY 2008, VOL. 24…”
Section: Instrumentmentioning
confidence: 99%
“…3 They have subsequently been utilized for the identification of paint and leather, 4 glass and ceramics, 5 steel, 6 daily necessaries, such as printing paper, business cards, cinnabar seal inks, aluminum foils and wrapping films. 3,7,8 Environmental reference samples, 9 rice and rice bran 10 were also analyzed. By using of an X-ray fluorescence setup with a pyroelectric X-ray emitter and a diskshaped secondary target, Ida and Kawai succeeded in the quantitative analysis of Cr in steel (% level).…”
Section: Introductionmentioning
confidence: 99%
“…With regard to paint analysis, Moioli et al [1], Ferrero et al [2], Cesareo et al [3], and Szfkefalvi-Nagy et al [4] reported applications to art objects. Analysis of paint by a pyroelectric X-ray generator, which is a portable X-ray generator driven by a dry battery, was also reported [5,6]. With regard to steel analysis, identification by a pyroelectric X-ray generator was reported [7], which demonstrated a possibility of on-site screening of steel.…”
Section: Introductionmentioning
confidence: 95%
“…However, there have been few reports on applications of portable XRF spectro- meters to forensic samples [13]. Identifications of cinnabar seal ink [14], leather [15], steel [16], and paint [17] by a pyroelectric X-ray generator were reported. These reports demonstrated that an X-ray source powered by a dry battery could be used for on-site screening.…”
Section: Introductionmentioning
confidence: 99%